POTENSI WISATA ALAM AIR TERJUN DI DESA MALANGGA KECAMATAN GALANG KABUPATEN TOLI TOLI - h, Herman; Sudhartono, Arief (Jurnal Warta Rimba, 2019)
The Republic of Indonesia is a country that has abundant natural resource potential, biodiversity and history. In the Toli toli area Especially in the village of Malangga there are waterfalls, rivers, flora and fauna, customs / culture that are feasible to be developed as nature tourism. But until now there has never been an identification and assessment of natural tourism potentials in Malangga Village so that it is feasible to be developed as a natural tourism destination. This research was conducted for 2 months, from April to May 2019, located in Malangga Village, Galang District, Toli-Toli Regency, Central Sulawesi Province. This study uses a survey method by conducting field observations directly accompanied by interviews with the community, with a sample of 31 sufficient to represent this study it's just that the representation of the elements of society used as research samples, data analysis used is the Guidelines for Regional Operations Analysis of Objects and Attraction Nature Tourism (ODO-ODTWA) Director General of PHKA 2003. The results showed that the potential of natural tourism found in the village of Malangga is a panorama of nature, waterfalls, rivers, traditional customs / cultures, flora and fauna. The results of the feasibility analysis of the potential values obtained for each criterion are attractiveness (100%), Accessibility (83.3%), Accommodation (50%), Facilities and Infrastructure (100%). Shows that Malangga Village is worthy of being developed as one of the natural tourist destination areas with a general feasibility percentage of 83.32%.Keywords : Potential, Potential Of Natural Tourism, Waterfall